2017
DOI: 10.3389/fpls.2017.01202
|View full text |Cite
|
Sign up to set email alerts
|

Drought Tolerance in Pinus halepensis Seed Sources As Identified by Distinctive Physiological and Molecular Markers

Abstract: Drought is one of the main constraints determining forest species growth, survival and productivity, and therefore one of the main limitations for reforestation or afforestation. The aim of this study is to characterize the drought response at the physiological and molecular level of different Pinus halepensis (common name Aleppo pine) seed sources, previously characterized in field trials as drought-sensitive or drought-tolerant. This approach aims to identify different traits capable of predicting the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 53 publications
3
26
0
2
Order By: Relevance
“…Proline is one of the most typical compatible solutes in plants [68] and it has been reported to significantly increase in many plant species, including conifers, under different abiotic stress conditions. For example, drought or salinity treatments have been shown to cause Pro accumulation in pine species [69][70][71], or in spruce [27,49,72]. In one-month-old plantlets of Larix × eurolepis Henry (Larix decidua × Larix kaempferi) grown in the presence of cadmium, Pro contents were reported to increase about three-fold over control values [73], similarly to what we have detected in the present study in salt-treated European larch seedlings.…”
Section: Osmolyte Synthesissupporting
confidence: 87%
“…Proline is one of the most typical compatible solutes in plants [68] and it has been reported to significantly increase in many plant species, including conifers, under different abiotic stress conditions. For example, drought or salinity treatments have been shown to cause Pro accumulation in pine species [69][70][71], or in spruce [27,49,72]. In one-month-old plantlets of Larix × eurolepis Henry (Larix decidua × Larix kaempferi) grown in the presence of cadmium, Pro contents were reported to increase about three-fold over control values [73], similarly to what we have detected in the present study in salt-treated European larch seedlings.…”
Section: Osmolyte Synthesissupporting
confidence: 87%
“…Taïbi [31] reported that free amino acids concentration could be used as a trait to identify the ability of Pinus halepensis in seedlings to cope with drought stress. The results of the present study showed that the concentration of proline in the roots, stems, and leaves increased under water stress with both moderate and severe water restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…They are diverse, however, and some like carotenoids and anthocyanins are known to play a role in photo-protection from oxidative stress resulting from various forms of abiotic stresses. There is a variation of photosynthetic pigments related to plants' phenology [52], but their reduction under water deficit conditions is common due to the reduction of chlorophyll synthesis, the inhibition of primary enzymes involved in photosynthesis, but also due to their degradation by chlorophyllase [53,54], and has been reported in several coniferous species under drought stress [41,[55][56][57][58]. The levels of photosynthetic pigments proved to be a reliable salt stress marker in European larch [40].…”
Section: Discussionmentioning
confidence: 99%
“…Besides its direct role in osmoregulation, Pro is involved in the protection of enzymes against denaturation and stabilization of protein synthesis, or may act as low-molecular weight chaperone, reactive oxygen species (ROS) scavenger or signaling molecule [59][60][61]. A strong increase in Pro under drought has been reported in many coniferous species, such as spruce [41,62], or pine [58,63], and fir [64]. In the genus Larix, a three-fold Pro increase has been reported in the hybrid L. x eurolepis when exposed to cadmium, or four-to seven-fold increase in L. decidua when exposed to salinity [65].…”
Section: Discussionmentioning
confidence: 99%